Analysis of factors related to the high choice of injectable contraceptives by acceptors - Setyabudhi, Mandhareta; Kabuhung, Elvine Ivana; Nuwindry, Iwan; Iswandari, Novita Dewi (Health Sciences International Journal, 2024)
Background: Three-monthly injectable contraception is a contraceptive method that works by releasing the hormone progesterone into the bloodstream. The impact of using injectable contraception is that menstrual disorders are often found, and fertility is delayed by four to five months. In 2023, 37.3% of acceptors chose three-monthly contraceptive injections, 18.4% pills, 15.2% implants, 14.2% monthly injections, 8.6% intrauterine device, 6.1% condoms, and tubectomy of 0.4%. Objective: Analysis of factors related to the high choice of injection contraceptives by acceptors. Method: Quantitative analytical survey research with a cross-sectional approach was conducted to assess age groups, education levels, parity, level of knowledge, and attitudes in choosing injectable contraception. Data were collected using a questionnaire and analyzed using the Chi-square and Fisher's exact tests. Results: The largest number of contraceptive acceptors were 20 people of early childbearing age, 26 people with elementary and middle school education, 27 people with multipara, 22 people with good knowledge, and 30 people with a positive attitude. The choice of contraceptive device is related to age (p=0.021), education level (p=0.021), parity (p=0.017), level of knowledge (p=0.009), and attitude (p=0.024) of the acceptor. Conclusion: Age, education level, parity, level of knowledge, and attitudes are factors that influence the choice of injectable contraceptive acceptors.